Femtosecond X‐ray diffraction from an aerosolized beam of protein nanocrystals. Issue 1 (26th January 2018) - Awel, Salah; Kirian, Richard A.; Wiedorn, Max O.; Beyerlein, Kenneth R.; Roth, Nils; Horke, Daniel A.; Oberthür, Dominik; Knoska, Juraj; Mariani, Valerio; Morgan, Andrew; Adriano, Luigi; Tolstikova, Alexandra; et al.
Abstract : A new particle‐injection approach is demonstrated that achieves very low background in the measurement of diffraction from macromolecular nanocrystals by using an aerosol‐focusing injector with an X‐ray free‐electron laser. Abstract : High‐resolution Bragg diffraction from aerosolized single granulovirus nanocrystals using an X‐ray free‐electron laser is demonstrated. The outer dimensions of the in‐vacuum aerosol injector components are identical to conventional liquid‐microjet nozzles used in serial diffraction experiments, which allows the injector to be utilized with standard mountings. As compared with liquid‐jet injection, the X‐ray scattering background is reduced by several orders of magnitude by the use of helium carrier gas rather than liquid. Such reduction is required for diffraction measurements of small macromolecular nanocrystals and single particles. High particle speeds are achieved, making the approach suitable for use at upcoming high‐repetition‐rate facilities.